An expanded mouse testis transcriptome and mass spectrometry defines novel proteins. Issue 1 (January 2020) - Gamble, Jaya; Chick, Joel; Seltzer, Kelly; Graber, Joel H; Gygi, Steven; Braun, Robert E; Snyder, Elizabeth M
Abstract : The testis transcriptome is exceptionally complex. Despite its complexity, previous testis transcriptome analyses relied on a reductive method for transcript identification, thus underestimating transcriptome complexity. We describe here a more complete testis transcriptome generated by combining Tuxedo, a reductive method, and spliced-RUM, a combinatorial transcript-building approach. Forty-two percent of the expanded testis transcriptome is composed of unannotated RNAs with novel isoforms of known genes and novel genes constituting 78 and 9.8% of the newly discovered transcripts, respectively. Across tissues, novel transcripts were predominantly expressed in the testis with the exception of novel isoforms which were also highly expressed in the adult ovary. Within the testis, novel isoform expression was distributed equally across all cell types while novel genes were predominantly expressed in meiotic and post-meiotic germ cells. The majority of novel isoforms retained their protein-coding potential while most novel genes had low protein-coding potential. However, a subset of novel genes had protein-coding potentials equivalent to known protein-coding genes. Shotgun mass spectrometry of round spermatid total protein identified unique peptides from four novel genes along with seven annotated non-coding RNAs. These analyses demonstrate the testis expresses a wide range of novel transcripts that give rise to novel proteins.